2008
DOI: 10.1155/2008/917492
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiology and Imaging of Visual Cortical Functions in the Blind: A Review

Abstract: Abstract. Imaging, transcranial magnetic stimulation, and psychophysiological recordings of the congenitally blind have confirmed functional activation of the visual cortex but have not extensively explained the functional significance of these activation patterns in detail. This review systematically examines research on the role of the visual cortex in processing spatial and non-visual information, highlighting research on individuals with early and late onset blindness. Here, we concentrate on the methods u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…A number of studies using neuroimaging technology have provided evidence of cortical reorganisation in humans deprived of vision (Sadato et al, 1996) and audition (Finney et al, 2001;Simon-Dack et al, 2008). For example, more than a decade ago, Sadato et al, used PET to show that the occipital cortex of people blinded at an early age is activated when they read Braille.…”
Section: Crossmodal Interactions and Sensory Deprivationmentioning
confidence: 99%
“…A number of studies using neuroimaging technology have provided evidence of cortical reorganisation in humans deprived of vision (Sadato et al, 1996) and audition (Finney et al, 2001;Simon-Dack et al, 2008). For example, more than a decade ago, Sadato et al, used PET to show that the occipital cortex of people blinded at an early age is activated when they read Braille.…”
Section: Crossmodal Interactions and Sensory Deprivationmentioning
confidence: 99%
“…During the non-visual spatial-related tasks, the occipital cortex has frequently been found to be activated in the early blind (EB) (Arnott et al, 2013), such as middle temporal area (MT) activation in motion discrimination and dorsal visual pathway activation in spatial discrimination and navigation (Cohen et al, 1997; Weeks et al, 2000; Vanlierde et al, 2003; Gougoux et al, 2005; Poirier et al, 2006; Ricciardi et al, 2006; Voss et al, 2006; Kupers et al, 2010; Matteau et al, 2010; Gagnon et al, 2012). The cross-modal activation of the occipital cortex has been associated with the superior non-visual spatial abilities in the EB (Gougoux et al, 2005; Simon-Dack et al, 2008). Furthermore, early studies had reported newly established anatomical connectivities (Bridge et al, 2008) between the subcortical visual relays and the intact visual areas, and reshaped effective connectivities (Silvanto et al, 2007, 2009) in both the ipslesional and contralesional spared visual areas after cortical blindness.…”
Section: Introductionmentioning
confidence: 99%